Cognitive assessment using the revised Hasegawa's dementia scale to determine the mid-term outcomes following transcatheter aortic valve replacement. Issue 3 (September 2019) - Saji, Mike; Tobaru, Tetsuya; Higuchi, Ryosuke; Hagiya, Kenichi; Takamisawa, Itaru; Shimizu, Jun; Iguchi, Nobuo; Takanashi, Shuichiro; Takayama, Morimasa; Isobe, Mitsuaki
Highlights: Cognitive function is known as a predictor to guide patient selection in TAVR. This study investigated if the HDS-R could predict long-term outcomes after TAVR. Patients with HDS-R ≤23 were sicker and more frail population. The HDS-R could independently predict long-term outcomes following TAVR. Abstract: Background: Several predictors are available to guide patient selection for transcatheter aortic valve replacement (TAVR) to achieve better outcomes, and cognitive function is one of these predictors. This study investigated whether the revised Hasegawa's dementia scale (HDS-R) could independently predict mid-term outcomes following TAVR. Methods: The study population comprised 455 patients with severe aortic stenosis who underwent TAVR at the Sakakibara Heart Institute between 2010 and 2018. The primary endpoint was all-cause mortality following TAVR. Patients were dichotomized into two groups according to the receiver operating characteristic analysis (HDS-R ≤23 and >23). Results: Patients with HDS-R ≤23 were older, were more frail, were more likely to have peripheral artery disease, had lower serum albumin levels, had lower ejection fractions, and had smaller aortic valve areas than those with HDS-R >23. By definition, 81 of the 455 patients (17.8%) were considered to have dementia (HDS-R ≤20) before TAVR. The discriminatory performance for predicting all-cause mortality at 3 years was greater for dichotomization with 23/24 than that with 20/21 [area under the curve (AUC): 0.63, 95% confidence interval (CI): 0.50–0.76, p = 0.047 vs. AUC: 0.52, 95% CI: 0.39–0.65, p = 0.713]. From the Kaplan–Meier analysis, patients with HDS-R ≤23 had higher mortality rates than those with HDS-R >23 (86.8 ± 3.3% and 75.4 ± 4.7% at 3 years, respectively; log-rank p = 0.001). The multivariate Cox regression analysis found that the HDS-R was independently associated with all-cause mortality (hazard ratio 2.11, 95% CI 1.21–3.69, p = 0.008). Conclusions: Patients with HDS-R ≤23 were sicker and more frail and had greater cognitive impairment. Additionally, HDS-R could independently predict mid-term outcomes following TAVR.